2014
DOI: 10.1159/000366469
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carotid Intima-Media Thickness in Predicting Longitudinal Cognitive Function in an Older Adult Cohort

Abstract: Background and Purpose: Carotid atherosclerosis is a risk factor for cerebrovascular disease in older adults. Although age-related cognitive decline has been associated with cerebrovascular disease, not much is known about the consequences of carotid atherosclerosis on longitudinal cognitive function. This study examines the longitudinal relationship between atherosclerosis and cognition in a sample of non-demented older subjects using baseline measurements of carotid intima media thickness (CIMT) and annual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
(25 reference statements)
1
22
0
1
Order By: Relevance
“…Vascular cognitive impairment has been the subject of intensive research in adults. 4 7 , 20 The aetiology of vascular cognitive impairment is multifactorial. Structural pathology and hemodynamic abnormalities, like cerebral hypoperfusion and impaired cerebral vasomotor reactivity, are the main causes of cognitive decline in patients with atherosclerosis or other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular cognitive impairment has been the subject of intensive research in adults. 4 7 , 20 The aetiology of vascular cognitive impairment is multifactorial. Structural pathology and hemodynamic abnormalities, like cerebral hypoperfusion and impaired cerebral vasomotor reactivity, are the main causes of cognitive decline in patients with atherosclerosis or other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 4 6 Executive cognitive functions were more disturbed than memory functions. 7 A possible pathophysiological mechanism for this cognitive decline may be impaired hemodynamic and microvascular function of the brain caused by atherosclerosis. 8 An excessive accumulation of fat in visceral and other organs severely disturbs the metabolism, leading to metabolic syndrome and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large cohort autopsy found that 77% of 410 AD subjects had grossly apparent circle of Willis atherosclerosis, which occurred more often than in non-AD subjects [129]. In non-demented patients, the carotid intima-media thickness, a marker of atherosclerosis, was found to be inversely related to annual cognitive measures of executive function [130]. A large population-based study of 4,371 stoke-free middle-aged patients found that atherosclerosis could predict future lower cognitive scores after 7 years [131].…”
Section: Vascular Risk Factors Lifestyle and Environmentmentioning
confidence: 99%
“… 8 , 9 In several studies (total n = 12,887), the presence of carotid atheroma as indicated by plaque area or intima-media thickening (IMT), but not luminal narrowing was associated with declining cognitive function or dementia. 10 13 The Framingham study (n = 1975) found variable associations between carotid IMT or stenosis > 50% and cognitive function or WMH. 14 However, carotid endarterectomy to remove tight stenosis did not influence cognitive decline five years later.…”
Section: Introductionmentioning
confidence: 99%